2002
DOI: 10.1002/1439-7633(20020301)3:2/3<257::aid-cbic257>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Uptake Studies with -Peptides

Abstract: Translocation across the membrane into cells is possible for certain peptides and proteins. To investigate the structural requirements of β‐peptides for this process, a series of fluorescein‐labeled β‐peptides has been synthesized and their cellular uptake into 3T3 mouse fibroblast cells determined by fluorescence microscopy (see picture). Polycationic β‐peptides have been shown to internalize into cells, and accumulation in the cytosol and nucleus is observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
101
2
3

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 148 publications
(108 citation statements)
references
References 7 publications
2
101
2
3
Order By: Relevance
“…Early mechanistic studies on the cellular entry of PTDs were performed with fixed cells (11,13,(22)(23)(24)(25)(26)(27)(28). Fixation is believed to permeate membranes (30), and allows vesicle-entrapped peptides and proteins to travel to new locations (29,30,32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early mechanistic studies on the cellular entry of PTDs were performed with fixed cells (11,13,(22)(23)(24)(25)(26)(27)(28). Fixation is believed to permeate membranes (30), and allows vesicle-entrapped peptides and proteins to travel to new locations (29,30,32).…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of a lipid bilayer, penetratin appears to form an amphipathic α-helix, which facilitates its insertion into the bilayer (44,45). HIV TAT peptide has likewise be found in a helical structure by NMR spectroscopy, suggesting that HIV TAT and perhaps other PTDs could act in a manner similar to penetratin (46).Early mechanistic studies on the cellular entry of PTDs were performed with fixed cells (11,13,(22)(23)(24)(25)(26)(27)(28). Fixation is believed to permeate membranes (30), and allows vesicle-entrapped peptides and proteins to travel to new locations (29,30,32).…”
mentioning
confidence: 99%
“…The studies reported here rep- 2 An attempt was made to conduct live cell studies as part of the previous study (10), but subsequent experiments have revealed that the conditions employed led to rapid cell death. Rueping et al (11) have reported cell entry by a ␤-homoarginine oligomer, and García-Echeverría and Ruetz (12) have reported entry by ␤-homolysine oligomers. 4 into the cytoplasm and nucleus of cells.…”
Section: Discussionmentioning
confidence: 99%
“…Some ␤-peptides possess antimicrobial activities (4,5,25,38), bind to the human somatostatin receptor (12,21), function as inhibitors of human immunodeficiency virus type 1 replication (39), and inhibit p53-hDM2 interaction (18). Cationic ␤-peptides cross bacterial and mammalian cell membranes and can be considered a new group of cell-penetrating peptides (13,26,31). Because they are able to form different helices (11) and to mimic amphipathic ␣-peptidic helices and turns (7,41), ␤-peptides have a high potential for being developed as novel pharmaceutically active substances that function as stable peptidomimetics (21,30,34).…”
mentioning
confidence: 99%